ANALISIS PERJANJIAN KERJASAMA DAN POLA PERBANDINGAN PENYELESAIAN SENGKETADI LUAR PENGADILAN - salam, safrin (Jurnal Hukum Volkgeist, 2017)
The contract or agreement is rapidly growing at this time as the consequence logical from the development cooperation business people business. Many business cooperation carried out by businessmen in the form of a contract or written agreement. The purpose of this research is to know and understand the legal analysis against the risks that arise in the agreement as well as to know the form of resolving disputes outside of the courts in the perspective of positive law and Islamic law. The type of research used in this study are normative legal research which in the use of research analysis Techniques used are qualitative techniques for which information unearthed through in-depth interviews and information search through the library, either from legislation, documents relating to the writing of this thesis so that what is in question in the study answered with a maximum. Results of the study showed that a cooperation agreement with Sejahtera Corporateand Adil Makmur potentially cause conflict so that it appears in the dispute between the parties resulting from any such agreement surfaced that there are risks such as risks language, the risk of disputes. To resolve this issue then there needs to be a model of dispute resolution that is ADR in particular using arbitration institutions while the Model dispute resolution outside of court according to ACT No. 30 of 1999 are mediation, arbitration, consilition, which chosen by the parties in accordance with applicable LAW while according to customary law, the dispute could be resolved through private, family, head of the indigenous organizational institution.